Characterization Of Alkaloids From The Leaves Of Psychotria Malayana Jack Of Lombok Island On The Basis Of Gas Chromatography-Mass Spectroscopy - Hadi, Surya; Rahmawati, Khairul Pahmi; Asnawati, Dina; Ersalena, Vera Fitriya; Azwari, Ahmadun (Chemistry Department, The University of Brawijaya, 2014)
The genus Psychotria is well known as a source of alkaloids and has contributed several novel indole-type alkaloids with quite a broad spectrum of bioactivities. This study was focused on identifying the alkaloids from the leaves of P. malayana Jack from Lombok island on the basis of Gas Chromatography-Mass Spectroscopy (GC-MS) data and the sample preparation followed acid-base extraction. The study showed that the major alkaloid contained by the leaves was hodgkinsine and other minor compounds, namely calycanthine, chimonantine, 2-ethyl-6-methylpyrazine, and 3-methyl-1,2,3,4-tetrahydro-gamma-carboline. Bioactivities of the compounds were also discussed.